Debris Index Before and After Apple Consumption - Nabila, Nuraini Khansa; Fadjeri, Indrayati; Purnama, Tedi; Noviani, Nita (Journal Center of Excellent : Health Assistive Technology, 2024)
Dental caries is a form of tooth decay that begins in the enamel and progresses to the dentin. This is usually caused by poor oral hygiene, which causes a buildup of debris that harbors various types of bacteria. Efforts to prevent debris accumulation can be in the form of mechanical control, chemical control and control of fibrous foods such as apples Purpose: The purpose of this study was to analyze the effectiveness of the debris index before and after consuming apples. Methods: The type of research used in this study was a quasy experiment with a pretest and posttest design with one group design. This research was conducted with a sample of 84 students, using a total sampling technique, the research data used primary data. The research instrument uses a debris index check sheet. Data analysis was tested using paired sample t test.  Results: Before entering the apples, 14 students (16.7%) had good debris criteria, 66 students (78.6%) had moderate debris criteria and 4 students (4,8%). And after consuming apples, 77 students (91.7%) had good debris criteria index, 7 students (8.3%) had moderate debris criteria index and no students had bad debris criteria index. Conclusion: The Debris Index before consuming apples was highest in the Moderate mixture of 66 students (78.6%). The Debris index after consuming apples was the highest in a good assessment of 77 students (91.7% and there were no bad criteria of 0.0%, the number of students who consumed apples was 86.9%, the highest with a good assessment of (91.7%), with the results of paired sample t-test p<0.001. Conclusion: Consuming apples is effective in reducing the debris index.